Noninferiority and Equivalence Evaluation of Clinical Performance among Computed Radiography, Film, and Digitized Film for Telemammography Services - Antonio J. Salazar; Javier A. Romero; Oscar A. Bernal; Angela P. Moreno; Sofía C. Velasco; Xavier A. Díaz (International Journal of Telemedicine and Applications)
Objective. The aim of this study was to evaluate and compare the clinical performance of different alternatives to implement low-cost screening telemammography. We compared computed radiography, film printed images, and digitized films produced with a specialized film digitizer and a digital camera. Material and Methods. The ethics committee of our institution approved this study. We assessed the equivalence of the clinical performance of observers for cancer detection. The factorial design included 70 screening patients, four technological alternatives, and cases interpreted by seven radiologists, for a total of 1,960 observations. The variables evaluated were the positive predictive value (PPV), accuracy, sensitivity, specificity, and the area under the receiver operating characteristic curves (AUC). Result. The mean values for the observed variables were as follows: accuracy ranged from 0.77 to 0.82, the PPV ranged from 0.67 to 0.68, sensitivity ranged from 0.64 to 0.74, specificity ranged from 0.87 to 0.90, and the AUC ranged from 0.87 to 0.90. At a difference of 0.1 to claim equivalence, all alternatives were equivalent for all variables. Conclusion. Our findings suggest that telemammography screening programs may be provided to underserved populations at a low cost, using a film digitizer or a digital camera.